2016
DOI: 10.1002/clc.22541
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Burden of Adult Congenital Heart Disease in US Emergency Departments

Abstract: Background: We assessed trends in incidence, in-hospital mortality, and admission among patients with adult congenital heart disease (ACHD) presenting to the emergency department (ED) from 2006 to 2012. Hypothesis: There is a considerable burden of ACHD in the US EDs. Methods: We used the 2006-2012 US Nationwide Emergency Department Sample. All ED visits with ACHD were identified using standard International Classification of Diseases, Ninth Edition, Clinical Modification codes. Results: The number of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 13 publications
4
23
0
Order By: Relevance
“…In 2014, the prevalence of ACHD in our study was 2.17 per 1000 adults, which is within the previous reported estimated range (1.7–6.12 per 1000) 1, 3, 4, 5, 6. In most high‐income countries in which care for ACHD is increasingly structured, prevalence of severe ACHD would increase over time 3, 4, 11. As revealed in the report from Quebec, severe ACHD accounted for 9% and 10.13% of the CHD population in 2000 and 2010, respectively 3, 4.…”
Section: Discussionsupporting
confidence: 84%
“…In 2014, the prevalence of ACHD in our study was 2.17 per 1000 adults, which is within the previous reported estimated range (1.7–6.12 per 1000) 1, 3, 4, 5, 6. In most high‐income countries in which care for ACHD is increasingly structured, prevalence of severe ACHD would increase over time 3, 4, 11. As revealed in the report from Quebec, severe ACHD accounted for 9% and 10.13% of the CHD population in 2000 and 2010, respectively 3, 4.…”
Section: Discussionsupporting
confidence: 84%
“…These urgent cardiac complaints are consistent with a nationwide study of ED use among ACHD patients and are particularly important given the increasing burden in ED utilization among patients with ACHD. 5 Multiple mechanisms may account for this association. One explanation is that patients who miss appointments receive delayed cardiac care, increasing the likelihood of otherwise preventable health crises and ED visits.…”
Section: Discussionmentioning
confidence: 99%
“…Insight into the relationship between clinic attendance and patient outcomes may help reduce the health care burden of this growing population. There has been a steady increase in health care utilization by ACHD patients over the last two decades, with rising numbers of costly ED visits and hospitalizations . Between 1998 and 2005, there has been a progressive increase in the number of emergency department visits in the United States by ACHD patients, and the number of hospital admissions has more than doubled .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Gurvitz et al found an increased likelihood of emergency department (ED) visits among CHD patients during the young adult transition period and that more than one‐third of ACHD admissions originated from the ED, nearly doubling that of adolescent CHD patients . More recently, Agarwal et al found that ED visits continue to increase for the ACHD population with an increased rate of admissions for even simple CHD lesions . In contrast, among ACHD patients who received recommended care in accordance with the Canadian Cardiac Society and the AHA/ACC 32nd Bethesda guidelines, Mylotte et al showed reduction in morbidity and mortality …”
Section: Discussionmentioning
confidence: 99%